Substance Use as a Mechanism for Social Inclusion among Gay, Bisexual, and Other Men Who Have Sex with Men in Vancouver, Canada. (15th October 2019) - W. Hawkins, Blake; Armstrong, Heather L.; Kesselring, Sarah; Rich, Ashleigh J.; Cui, Zishan; Sereda, Paul; Howard, Terry; Forrest, Jamie I.; Moore, David M.; Lachowsky, Nathan J.; Hogg, Robert S.; Roth, Eric A.
Abstract: Background : Previous research demonstrates that substance use preferences and social-sexual environments are highly interrelated for gay, bisexual, and other men who have sex with men (gbMSM). Objective : We conducted a qualitative study to explore the socio-cultural context of substance use among local gbMSM communities in Metro Vancouver, Canada. Methods : Twenty gbMSM were purposively sampled from the larger Momentum Health Study cohort, a sexual health study of gbMSM in Greater Vancouver. Participants were demographically diverse in terms of HIV serostatus, age, income, ethnicity, and area of residence within the city and neighboring suburbs. Community maps generated by participants during formative research served as prompts for semi-structured interviews which were audio recorded and transcribed verbatim. Thematic analysis identified three themes of common experience. Results : First, participants indicated that substance use is intrinsically social in Vancouver gbMSM communities and that it functions as both a means of social inclusion and exclusion. Second, a distinction was made between types of substances and the location and context of their use, with specific substances having particular uses and meanings. Third, analysis suggested that gbMSM change their substance use over the life course and that this is affected by shifting priorities as people age. Discussion : For Vancouver gbMSM communities, substance use serves several social-cultural functions and can simultaneously serve as both a potential facilitator and barrier for community connection. Future research and health programing should consider venue and context specific messaging and recognize the heterogeneity of substance use within the larger gbMSM population.